A negative electrode binder, a negative electrode sheet, a battery

CN122941322APending Publication Date: 2026-10-20SHENZHEN HAODYNE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611245212.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

本发明提供的负极粘结剂兼具刚性支撑、柔性形变缓冲、界面绑定、自修复稳界面及抗溶胀性能,有助于解决传统负极粘结剂结构单一、形变适配差、界面不稳、循环衰减快的痛点,大幅提升硅碳负极的循环稳定性

Benefits of technology

[0023]本发明提供的负极粘结剂兼具刚性支撑、柔性形变缓冲、界面绑定及抗溶胀性能。其中,脂肪族丙烯酸酯类结构单元赋予粘结剂优异延展性能,有效缓冲硅碳材料充放电过程中的大体积形变,分散应力集中;脂环族丙烯酸酯类结构单元凭借刚性骨架限制分子链段内旋转,提升粘结剂热稳定性与抗电解液溶胀性能,平衡体系刚韧性;界面活化结构单元与含羟基的丙烯酸酯类结构单元协同作用,通过氢键与共价键双重作用强化固-固界面结合,同时提供充足极性反应位点优化交联网络均匀性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_22
    Figure SMS_22
  • Figure SMS_23
    Figure SMS_23
  • Figure SMS_24
    Figure SMS_24
Patent Text Reader

Abstract

This invention provides a negative electrode binder, a negative electrode sheet, and a battery. The negative electrode binder comprises a polymer; the polymer includes olefinic structural units, aliphatic acrylate structural units, alicyclic acrylate structural units, hydroxyl-containing acrylate structural units, interface-activating structural units, and organic crosslinking structural units; the interface-activating structural units include anhydride structural units. The negative electrode binder provided by this invention combines rigid support, flexible deformation buffering, interface bonding, self-healing interface stabilization, and anti-swelling properties, helping to solve the pain points of traditional negative electrode binders such as simple structure, poor deformation adaptability, unstable interface, and rapid cycle decay, and significantly improving the cycle stability of silicon-carbon negative electrodes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new energy batteries, and more particularly to a negative electrode binder, a negative electrode sheet, and a battery. Background Technology

[0002] As the new energy industry continues to demand higher energy density from lithium-ion batteries, silicon-carbon composite materials, with their ultra-high theoretical specific capacity of 4200 mAh / g (combined with the excellent conductivity and volume buffering effect of carbon materials), have become the mainstream technology for next-generation high-energy-density lithium battery anodes. However, silicon-based materials undergo repeated volume expansion and contraction of 300% to 400% during charge-discharge cycles, which can easily lead to active particle pulverization, electrode structure cracking, and continuous rupture and reconstruction of the solid electrolyte interface film, ultimately causing rapid capacity decay and a significant reduction in cycle life. Anode binders, as the core component maintaining the overall electrode structure and ensuring interfacial bonding strength, are key materials for overcoming the bottlenecks in the application of silicon-carbon anodes.

[0003] Existing negative electrode binders still have many performance shortcomings: polyvinylidene fluoride binders have low adhesion strength and poor toughness, making it difficult to buffer the large volume deformation of silicon carbon, and they require the use of toxic organic solvents for processing, resulting in insufficient environmental friendliness; pure linear polyacrylic acid binders have high rigidity and insufficient ductility, and the single carboxyl functional group cannot synergistically balance mechanical flexibility and interface control capabilities, making them prone to electrode powder shedding after long cycles; traditional modified acrylate binders have limited functions, and the network strength constructed by conventional difunctional crosslinking agents is limited, resulting in insufficient resistance to swelling and deformation; existing functional binders only introduce single functional monomers or single-component crosslinking systems, lacking multi-dimensional synergistic structural design, making it difficult to synergistically solve the problems of insufficient volume deformation adaptation, poor interface stability, weak resistance to swelling, and poor long-cycle performance.

[0004] Therefore, how to synergistically solve the problems of insufficient volume deformation adaptation, poor interface stability, weak anti-swelling ability and poor long-cycle performance in the development of silicon-carbon anode binders is a technical challenge that urgently needs to be overcome in this field. Summary of the Invention

[0005] This invention provides a negative electrode binder, a negative electrode sheet, and a battery. The negative electrode binder provided by this invention combines rigid support, flexible deformation buffering, interface bonding, self-healing interface stabilization, and anti-swelling properties, which helps to solve the pain points of traditional negative electrode binders such as simple structure, poor deformation adaptability, unstable interface, and rapid cycle decay, and significantly improves the cycle stability of silicon-carbon negative electrodes.

[0006] This invention provides a negative electrode binder comprising a polymer; the polymer comprises acrylate structural units, aliphatic acrylate structural units, alicyclic acrylate structural units, hydroxyl-containing acrylate structural units, interface-activated structural units, and organic crosslinking structural units; the interface-activated structural units include acid anhydride structural units.

[0007] According to one embodiment of the present invention, the mass ratio of the olefinic structural unit, the aliphatic acrylate structural unit, the alicyclic acrylate structural unit, the hydroxyl-containing acrylate structural unit, the interface-activated structural unit, and the organic crosslinking structural unit is (55~75):(10~20):(5~12):(2~5):(3~8):(0.5~4).

[0008] According to one embodiment of the present invention, the acrylic acid structural unit includes one or more of itaconic acid structural units, fumaric acid structural units, citraconic acid structural units, acrylic acid structural units, and methacrylic acid structural units.

[0009] According to one embodiment of the present invention, the aliphatic acrylate structural unit includes one or more of butyl acrylate structural units, ethyl acrylate structural units, and isooctyl acrylate structural units.

[0010] According to one embodiment of the present invention, the alicyclic acrylate structural unit includes one or more of the following: acrylic acid modified adamantane ester structural unit, isobornyl acrylate structural unit, and tricyclodecanediethanol diacrylate structural unit.

[0011] According to one embodiment of the present invention, the hydroxyl-containing acrylate structural unit includes one or more of isosorbide acrylate structural units and glyceryl acrylate structural units.

[0012] According to one embodiment of the present invention, the anhydride structural unit in the interface activation structural unit includes one or more of maleic anhydride structural units, succinic anhydride structural units, itaconic anhydride structural units, and methacrylic anhydride structural units.

[0013] According to one embodiment of the present invention, the polymer further includes inorganic crosslinking groups attached to the molecular chain of the polymer.

[0014] According to one embodiment of the present invention, the mass ratio of the organic crosslinking structural unit to the inorganic crosslinking group in the polymer is (1~5):1.

[0015] According to one embodiment of the present invention, the organic crosslinking structural unit includes one or more of the following: trimethylolpropane triacrylate structural unit, pentaerythritol triacrylate structural unit, dipropylene glycol diacrylate structural unit, and itaconic acid diacrylate structural unit.

[0016] According to one embodiment of the present invention, the inorganic crosslinking group includes a borate ester group.

[0017] According to one embodiment of the present invention, the glass transition temperature of the polymer is -5°C to 15°C.

[0018] According to one embodiment of the present invention, the viscosity of the negative electrode binder is 2000 mPa. s~20000mPa s.

[0019] According to one embodiment of the present invention, the solid content of the negative electrode binder is 15% to 25%.

[0020] In another aspect, the present invention provides a negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, the negative electrode active material layer comprising the aforementioned negative electrode binder.

[0021] In another aspect, the present invention provides a battery comprising the aforementioned negative electrode.

[0022] The implementation of this invention has at least the following beneficial effects:

[0023] The negative electrode binder provided by this invention combines rigid support, flexible deformation buffering, interfacial bonding, and anti-swelling properties. Specifically, the aliphatic acrylate structural units endow the binder with excellent ductility, effectively buffering the large-volume deformation of silicon-carbon materials during charging and discharging, and dispersing stress concentration; the alicyclic acrylate structural units, with their rigid skeleton, restrict rotation within molecular chain segments, improving the binder's thermal stability and anti-electrolyte swelling performance, balancing the system's rigidity and toughness; the interfacial activation structural units and the hydroxyl-containing acrylate structural units work synergistically, strengthening the solid-solid interface bonding through both hydrogen bonding and covalent bonding, while providing sufficient polar reaction sites to optimize the uniformity of the crosslinking network.

[0024] Organic cross-linked structural units help construct a permanent covalent cross-linked framework, providing basic structural support for the bonding system and further enhancing the deformation resistance and structural stability of the cross-linked network. The precise matching and synergistic effect of multi-functional structural units systematically solves the problems of traditional anode binders—such as single structure, poor deformation adaptability, unstable interfaces, and rapid cycle decay—at the molecular structure level, effectively maintaining the integrity of the electrode structure during long cycles and significantly improving the cycle stability of silicon-carbon anodes. Detailed Implementation

[0025] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. The specific embodiments listed below are merely descriptions of the principles and features of this invention, and the examples given are only for explaining this invention and are not intended to limit the scope of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0026] This invention provides a negative electrode binder comprising a polymer; the polymer comprises acrylate structural units, aliphatic acrylate structural units, alicyclic acrylate structural units, hydroxyl-containing acrylate structural units, interface-activated structural units, and organic crosslinking structural units; the interface-activated structural units include acid anhydride structural units.

[0027] According to the inventors' research, the aforementioned negative electrode binder utilizes a polymer system constructed through the synergistic design of multi-component structural units to systematically address the aforementioned defects at the molecular structure level. This invention introduces aliphatic acrylate structural units into the polymer backbone. Leveraging the high flexibility of their long alkyl side chains, these units endow the negative electrode binder with excellent ductility, effectively buffering the large volume deformation during the charging and discharging process of silicon-carbon materials, dispersing volume stress concentration, and preventing macroscopic cracking of the electrode due to repeated expansion and contraction. Simultaneously, the introduction of alicyclic acrylate structural units utilizes their rigid structure to restrict rotation within molecular chain segments, improving the thermal stability and resistance to electrolyte swelling of the negative electrode binder, balancing the rigidity and toughness of the system, and preventing a decrease in structural strength due to excessive flexible components. This invention further introduces hydroxyl-containing acrylate structural units. These units are rich in active hydroxyl polar groups, which on the one hand can form abundant hydrogen bonds with oxygen-containing groups on the surface of silicon / carbon active particles and current collectors, further enhancing the interfacial adhesion between the binder system and the electrode and active material, reducing interfacial desorption failure; on the other hand, they can serve as auxiliary crosslinking sites, synergistically optimizing the density and uniformity of the crosslinking network with the organic crosslinking structural units. By introducing interface-activated structural units, hydrogen bonds and covalent bonds can be formed with the hydroxyl groups on the surface of silicon / carbon active particles, significantly enhancing the solid-solid interface bonding strength. At the same time, it provides sufficient polar reaction sites for crosslinking reactions, optimizing the uniformity and crosslinking density of the crosslinking network.

[0028] In the negative electrode binder of this invention, the above-mentioned structural units work together to enable the negative electrode binder to simultaneously achieve excellent deformation adaptability, interfacial bonding strength, anti-swelling performance and self-healing ability. This effectively alleviates the defects of traditional negative electrode binders in silicon-carbon negative electrode applications, such as short cycle life, poor electrode structure stability and rapid electrochemical performance decay, and significantly improves the cycle stability and rate performance of silicon-carbon negative electrodes.

[0029] In some embodiments, the mass ratio of the above polymer to the acrylate structural unit, the aliphatic acrylate structural unit, the alicyclic acrylate structural unit, the hydroxyl-containing acrylate structural unit, the interface-activated structural unit, and the organic crosslinking structural unit is (55~75):(10~20):(5~12):(2~5):(3~8):(0.5~4).

[0030] In some embodiments, the mass ratio of the above-mentioned acrylate structural units to aliphatic acrylate structural units is (55~75):(10~20), for example, 55:10, 55:20, 75:10, 75:20, 65:15, or any combination thereof. A mass ratio of acrylate structural units to aliphatic acrylate structural units not exceeding 75:10 helps to introduce sufficient flexible segments, improve polymer ductility, and buffer the volume deformation of silicon-carbon materials. A mass ratio of acrylate structural units to aliphatic acrylate structural units not less than 55:20 helps to avoid an excessive amount of hydrophobic groups leading to a decrease in the proportion of polar bonding sites, maintaining the basic interfacial bonding strength. Controlling the mass ratio within the above range is beneficial for balancing bonding strength and deformation adaptability, alleviating the defects of traditional negative electrode adhesives being too rigid and having insufficient deformation buffering.

[0031] In some embodiments, the mass ratio of the above-mentioned acrylate structural units to alicyclic acrylate structural units is (55~75):(5~12), for example, 55:5, 55:12, 75:5, 75:12, 65:8, or any combination thereof. A mass ratio of acrylate structural units to alicyclic acrylate structural units not exceeding 75:5 helps to exert a rigid topological support effect, improve the anti-electrolyte swelling performance and thermal stability of the negative electrode binder, and disperse local stress during cycling. A mass ratio of acrylate structural units to alicyclic acrylate structural units not less than 55:12 helps to avoid excessive rigid groups leading to a decrease in the overall toughness of the binder and ensures deformation adaptability. Controlling the mass ratio within the above range is beneficial for balancing structural rigidity and ductility, and improving the problem of insufficient anti-swelling and anti-deformation capabilities of traditional binders.

[0032] In some embodiments, the mass ratio of the above-mentioned acrylate structural units to the hydroxyl-containing acrylate structural units is (55~75):(2~5), for example, 55:2, 55:5, 75:2, 75:5, 65:3, or any combination thereof. A mass ratio of acrylate structural units to hydroxyl-containing acrylate structural units not exceeding 75:2 helps to construct a sufficient dynamic hydrogen bond network, exert a self-healing effect on micro-damage, and alleviate the accumulation of micro-defects during cycling. A mass ratio of acrylate structural units to hydroxyl-containing acrylate structural units not less than 55:5 helps to avoid abnormal fluctuations in slurry viscosity due to excessive functional groups, ensuring the stability of the coating process. Controlling the mass ratio within the above range is beneficial for balancing self-healing function and processability, and alleviating electrode failure caused by microcrack propagation during cycling.

[0033] In some embodiments, the mass ratio of the above-mentioned olefinic structural unit to the interface-activated structural unit is (55~75):(3~8), for example, 55:3, 55:8, 75:3, 75:8, 65:5, or any combination thereof. A mass ratio of olefinic structural unit to interface-activated structural unit not exceeding 75:3 helps strengthen the solid-solid interface bonding strength, provides sufficient reaction sites for dynamic crosslinking, and improves interface stability. A mass ratio of olefinic structural unit to interface-activated structural unit not less than 55:8 helps avoid electrolyte side reactions caused by excessive polar groups and reduces the risk of increased interface impedance. Controlling the mass ratio within the above range is beneficial for balancing interface bonding strength and electrochemical stability, and improves the defects of weak interface bonding and rapid increase in cycling impedance in traditional negative electrode binders.

[0034] The mass ratio of the aforementioned olefinic structural units to organic crosslinked structural units is (55~75):(0.5~4), for example, 55:0.5, 55:4, 65:3, 75:0.5, 75:4, or any combination thereof. A mass ratio of no more than 75:0.5 helps to construct a basic covalent crosslinked framework, improving the structural stability and resistance to electrolyte swelling of the bonding system. A mass ratio of no less than 55:4 helps to avoid excessive crosslinking leading to hindered chain segment movement, ensuring the ductility and deformation adaptability of the negative electrode binder. Controlling the mass ratio within the above range is beneficial for constructing a permanently crosslinked network with appropriate density, balancing structural strength and deformation toughness.

[0035] It should be noted that the mass ratio of each structural unit in the polymer in this specification is basically consistent with the mass ratio of the corresponding monomers when preparing the polymer. This principle applies to the subsequent descriptions of the proportions of other structural units / groups, and will not be repeated here.

[0036] In some embodiments, the olefinic structural unit includes one or more of itaconic acid, fumaric acid, citraconic acid, acrylic acid, and methacrylic acid structural units. These olefinic structural units, serving as the main framework monomers, carry a high density of carboxyl groups, which can form multiple hydrogen bonds with hydroxyl groups and oxygen-containing defect sites on the surface of all negative electrode active materials. Simultaneously, they form coordination bonds with the oxide layer on the surface of the copper current collector, providing high-strength interfacial adhesion for the electrode and ensuring high peel strength and structural adhesion of the electrode sheet. The strong hydrophilicity of the carboxyl groups ensures uniform dispersion of the aqueous slurry and effectively inhibits the agglomeration of active particles. The methacrylic acid structural unit, with its methyl hydrophobic side chain, can improve the hydrolysis resistance and electrolyte aging resistance of the negative electrode binder, making it suitable for long-cycle energy storage batteries.

[0037] Specifically, the aforementioned olefinic structural units are derived from olefinic monomers, which include one or more of itaconic acid, fumaric acid, citraconic acid, acrylic acid, and methacrylic acid.

[0038] In some embodiments, the glass transition temperature (Tg) of the homopolymer corresponding to the aliphatic acrylate structural unit is -70℃ to -20℃, for example, a range of -70℃, -60℃, -50℃, -40℃, -30℃, -20℃, or any combination thereof. A glass transition temperature not lower than -70℃ helps avoid excessive chain segment flexibility leading to a low overall polymer modulus and insufficient structural support; a glass transition temperature not higher than -20℃ helps ensure sufficient chain segment flexibility, improves the ductility of the negative electrode binder, and buffers the volume deformation of the silicon-carbon material. Controlling this parameter within the above range helps balance the structural rigidity and deformation buffering capacity of the negative electrode binder, adapting to the large volume deformation conditions of the silicon-carbon negative electrode. In the embodiments of this invention, the glass transition temperature of the homopolymer corresponding to the aliphatic acrylate structural unit refers to the glass transition temperature measured by differential scanning calorimetry after the monomer corresponding to the structural unit is prepared into a homopolymer.

[0039] In some embodiments, the aliphatic acrylate structural units include one or more of butyl acrylate, ethyl acrylate, and isooctyl acrylate structural units. The butyl acrylate structural unit contains long alkyl flexible side chains. Introducing it into the polymer lowers the polymer's glass transition temperature, overcoming the inherent rigidity and poor ductility of pure polyacrylic acid, and endowing the negative electrode binder with reversible deformation capability, thus buffering the ultra-large volume stress of the silicon-carbon negative electrode. The introduction of the ethyl acrylate structural unit improves the structural rigidity of the negative electrode binder while maintaining good flexibility, preventing the electrode from being too soft and lacking sufficient mechanical strength, and adapting it to high-density electrodes. The isooctyl acrylate structural unit has a longer hydrophobic segment, which can further reduce the electrolyte swelling rate and improve high-temperature cycle stability, making it suitable for high-temperature silicon-carbon batteries. Through the optional design of various aliphatic acrylate flexible monomers, the flexibility of the chain segments and the anti-swelling properties can be flexibly controlled, helping to adapt to negative electrode materials with different expansion rates and different temperature application conditions, thus improving the system's versatility.

[0040] Specifically, the aforementioned aliphatic acrylate structural units are derived from aliphatic acrylate monomers, which include one or more of butyl acrylate, ethyl acrylate, and isooctyl acrylate.

[0041] In some embodiments, the alicyclic acrylate structural unit includes one or more of the following: acrylic-modified adamantane acrylate structural unit, isobornyl acrylate structural unit, and tricyclodecanediethanol diacrylate structural unit. All of the above structural units possess rigid structures. Among them, the acrylic-modified adamantane structural unit contains a cage-like adamantane three-dimensional rigid skeleton in its molecule. The corresponding monomer participates in free radical copolymerization through its own acrylic double bond, introducing the rigid structure into the copolymer side chain. This can construct uniform physical topological support sites, disperse local stress during electrode cycling, improve the thermal stability and anti-electrolyte swelling performance of the negative electrode binder, and optimize the regularity of molecular chain stacking. The isobornyl acrylate structural unit has asymmetric bicyclic bridged ring side groups, which are large in volume and have strong steric hindrance. After being incorporated into the polymer backbone, they will hinder the internal rotational movement of chain segments, which helps to improve the deformation resistance and high temperature resistance of the negative electrode binder. The tricyclic decanediethanol diacrylate structural unit has a tricyclic fused bridged ring skeleton, making it difficult for the molecular conformation to be flipped. Moreover, its bifunctional structure can directly form covalent cross-linking nodes during polymerization, embedding the rigid skeleton into the cross-linking network, further restricting chain segment movement. The effect of improving the rigidity of the system is better than that of monofunctional rigid monomers. Specifically, the aforementioned rigid structure refers to a ring structure that cannot undergo conformational expansion through rotation within a single bond. It includes types such as bridged rings, cage-like alicyclic rings, and fused rings. This type of ring structure forms a stable spatial configuration by sharing bridgehead carbon atoms, making it difficult for conformational inversion to occur. It can significantly restrict the segmental movement of the polymer backbone in the form of large-volume side groups.

[0042] Specifically, the aforementioned alicyclic acrylate structural units are derived from alicyclic acrylate monomers, including one or more of acrylic acid-modified adamantane ester, isobornyl acrylate, and tricyclodecanediethanol diacrylate. The raw material industrialization cost of these alicyclic acrylate monomers is low, and high-performance rigid modification can be achieved without relying on expensive modifying auxiliaries, thus breaking through the industry's cost barrier.

[0043] In some embodiments, the hydroxyl-containing acrylate structural units include one or more of isosorbide acrylate structural units and glyceryl acrylate structural units. More preferably, the isosorbide acrylate structural units include isosorbide monoacrylate structural units, and the glyceryl acrylate structural units include glyceryl monoacrylate structural units. These structural units possess a multi-hydroxyl cyclic topology; the multi-hydroxyl sites can construct a reversible dynamic hydrogen bond network between polymer molecular chains, endowing the negative electrode binder with micro-damage self-healing properties, enabling it to autonomously repair microstructural damage such as microcracks and micro-peeling generated during charge-discharge cycles; simultaneously, it can improve the interfacial compatibility between the negative electrode binder and the electrolyte, passivate active defect sites on the silicon-carbon surface, and induce the formation of a stable solid electrolyte interfacial film.

[0044] In this embodiment of the invention, the hydroxyl-containing acrylate structural unit refers to a structural unit formed by copolymerizing hydroxyl-containing acrylate monomers into the polymer backbone. This type of structural unit possesses both good copolymerization compatibility and functional regulation, and can achieve micro-damage self-repair and interface performance optimization in the cross-linked network by relying on its own multi-hydroxyl cyclic topology. Specifically, the aforementioned hydroxyl-containing acrylate monomers include one or more of isosorbide acrylate and glyceryl acrylate. More preferably, isosorbide acrylate includes isosorbide monoacrylate, and glyceryl acrylate includes glyceryl monoacrylate (CAS 10095-20-2).

[0045] In some embodiments, the aforementioned hydroxyl-containing acrylate monomers may include bio-based hydroxyl-containing acrylate monomers prepared from renewable biomass resources through biorefining or chemical modification. These monomers are green and environmentally friendly, and the raw materials are renewable, thus improving the bonding stability while also taking into account the environmental performance of the materials.

[0046] In some embodiments, the anhydride structural units in the interface activation structural units include one or more of maleic anhydride, succinic anhydride, itaconic anhydride, and methacrylic anhydride. The molecules of these structural units contain highly reactive polar anhydride groups, which can undergo esterification reactions with the hydroxyl groups on the surface of silicon particles to form covalent bonds. This further strengthens the interfacial bonding with the silicon-based active material, helps reduce the risk of active particle debonding during cycling, and improves the long-term stability of the electrode structure.

[0047] Specifically, the aforementioned anhydride structural units are derived from unsaturated anhydride monomers, which include one or more of maleic anhydride, succinic anhydride, itaconic anhydride, and methacrylic anhydride.

[0048] In some embodiments, the organic crosslinking structural unit includes one or more of the following: trimethylolpropane triacrylate structural unit, pentaerythritol triacrylate structural unit, tripropylene glycol diacrylate structural unit, and itaconic acid diacrylate structural unit. These structural units contain multiple polymerizable double bonds, which can crosslink with multiple polymer chains during polymerization to construct a dense and stable three-dimensional covalent network. This ensures the basic mechanical strength, structural stability, and anti-swelling properties of the negative electrode binder, and adapts to different polymer solids content systems.

[0049] Specifically, the aforementioned organic crosslinking structural unit is derived from an organic crosslinking agent, which includes one or more of trimethylolpropane triacrylate, pentaerythritol triacrylate, dipropylene glycol diacrylate, and itaconic acid diacrylate.

[0050] In some embodiments, the polymer further includes inorganic crosslinking groups attached to the polymer molecular chains; more preferably, the inorganic crosslinking groups include borate ester groups. Through the inorganic crosslinking groups between molecular chains, a reversible dynamic crosslinking network is constructed, endowing the negative electrode binder with micro-damage self-healing properties. It can autonomously repair microcracks and interfacial micro-delamination generated during cycling, while simultaneously achieving stress relaxation and adapting to repeated volumetric deformation of the silicon-carbon material.

[0051] Specifically, the aforementioned inorganic crosslinking groups are derived from inorganic crosslinking agents. Inorganic crosslinking agents include one or more of boric acid, metaboric acid, and borax. During the curing stage, the inorganic crosslinking agent reacts with the carboxyl and hydroxyl groups of the polymer side chains to form dynamic crosslinking bonds of borate esters, constructing a reversible dynamic crosslinking network that provides self-healing and stress relaxation capabilities.

[0052] In some embodiments, the mass ratio of organic crosslinking structural units to inorganic crosslinking groups is (1~5):1, for example, 1:1, 2:1, 3:1, 4:1, 5:1, or any combination thereof. A mass ratio not less than 1:1 helps to provide a sufficient permanent covalent crosslinking backbone, maintaining the structural stability and anti-swelling properties of the crosslinked network; a mass ratio not higher than 5:1 helps to ensure the proportion of dynamic crosslinking points, playing a role in stress relaxation and adaptive deformation; controlling the mass ratio within the above range is beneficial to constructing a rigid-flexible dual crosslinked network, synergistically alleviating the defects of insufficient strength or poor deformation adaptability of a single crosslinked system. Preferably, the mass ratio of organic crosslinking structural units to inorganic crosslinking groups is (2~4):1, for example, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, or any combination thereof.

[0053] In this invention, organic covalent cross-linking constructs a permanent three-dimensional rigid framework, locking the basic molecular structure and improving resistance to swelling and tensile strength; the dynamic borate ester bonds in the inorganic cross-linking groups can be reversibly broken and recombined with the expansion and contraction of silicon carbon, relaxing the interfacial stress in real time. The synergistic effect of the rigid and flexible dual networks perfectly adapts to the 300%~400% alternating deformation working conditions of silicon carbon anode.

[0054] In some embodiments, the glass transition temperature of the polymer is -5°C to 15°C, for example, a range of -5°C, -1°C, 5°C, 10°C, 15°C, or any combination thereof. A glass transition temperature not lower than -5°C helps maintain the basic modulus and structural rigidity of the cross-linked network, improving resistance to electrolyte swelling and electrode molding strength. A glass transition temperature not higher than 15°C helps retain sufficient chain segment mobility, ensuring the ductility and stress relaxation characteristics of the negative electrode binder, and meeting the requirements for volume deformation buffering. Controlling this parameter within the above range helps achieve a balance between the rigidity and flexibility of the cross-linked network, alleviating the defects of traditional negative electrode binders being either too brittle and prone to cracking or too soft and prone to swelling.

[0055] In some embodiments, the negative electrode binder further includes a solvent, including deionized water.

[0056] In some embodiments, the solid content of the negative electrode binder is 15% to 25%, for example, a range of 15%, 17%, 19%, 21%, 23%, 25%, or any combination thereof. A solid content of not less than 15% helps reduce transportation and storage costs, decreases the amount of water introduced during slurry preparation, and improves production efficiency; a solid content of not more than 25% helps maintain the uniformity and stability of the adhesive solution, controls the viscosity of the negative electrode binder, reduces the risk of agglomeration, and ensures batch-to-batch performance consistency; controlling the solid content within the above range is beneficial for balancing the economics of industrial production with product stability.

[0057] In some embodiments, the viscosity of the negative electrode binder at 20°C to 30°C is 2000 mPa. s~20000mPa s, for example 2000mPa s, 6000mPa s, 8000mPa s, 10000mPa s, 13000mPa s, 17000mPa s, 20000mPa The range consisting of s or any two of them. The viscosity of the negative electrode binder is not less than 2000 mPa. s helps improve the suspension stability of the slurry, reduces the risk of active particle sedimentation, and ensures uniform coating thickness; the viscosity of the negative electrode binder is not higher than 20000 mPa. s helps ensure the flow and dispersion properties of the slurry, reduces the difficulty of coating processing, and improves the surface smoothness of the electrode sheet; controlling the viscosity within the above range is beneficial for adapting to the industrial coating process window and improving the adaptability of production and processing.

[0058] Specifically, when the solid content of the negative electrode binder is 15%~20%, the viscosity of the negative electrode binder at 25°C is 2000 mPa. s~6000mPa s; When the solid content of the negative electrode binder is 20%~22%, the viscosity of the negative electrode binder at 25℃ is 6000mPa. s~8000mPa s; When the solid content of the negative electrode binder is 22%~25%, the viscosity of the negative electrode binder at 25℃ is 8000mPa. s~20000mPa s.

[0059] For example, the negative electrode binder provided in the embodiments of the present invention is prepared by the following method: a mixed monomer material containing an interface-activating monomer, a hydroxyl-containing acrylate monomer, an aliphatic acrylate monomer, an alicyclic acrylate monomer, and an olefinic monomer is mixed with an organic crosslinking agent to obtain a mixed reaction material; the mixed reaction material is subjected to a polymerization reaction; after the polymerization reaction is completed, an inorganic crosslinking agent is optionally added, and the mixture is cooled and filtered to obtain the negative electrode binder.

[0060] The negative electrode binder provided in this embodiment of the invention is prepared under the action of an initiator, which is added in batches and includes a first initiator and a second initiator.

[0061] The first and second initiators may be the same or different, and each is independently selected from thermally decomposable initiator systems and / or redox initiator systems. The thermally decomposable initiator systems are selected from one or more of ammonium persulfate, potassium persulfate, and sodium persulfate; the redox initiator systems are selected from ammonium persulfate and sodium bisulfite. These initiators, as the core for initiating aqueous-phase free radical polymerization, are suitable for all-aqueous low-temperature polymerization systems. Heating decomposes them to generate free radicals, which can smoothly initiate the copolymerization reaction of multiple monomers. The reaction rate is mild and controllable, with high monomer conversion and few residual impurities. This effectively avoids battery side reactions caused by unreacted monomers and toxic additives, ensuring the electrochemical stability of the electrodes.

[0062] Specifically, the initiator accounts for 0.4% to 1.2% of the total mass of the mixed monomers, for example, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, or any combination thereof. When the mass percentage is below 0.4%, the initiation efficiency is insufficient, resulting in low monomer conversion and a high amount of small molecule residue. When the mass percentage is above 1.2%, the free radical concentration is too high, easily leading to localized burst polymerization, uneven polymer molecular weight distribution, and poor performance stability. Preferably, it is 0.8%, which allows for stable and controllable polymerization, achieving an overall monomer conversion rate of over 99%, minimizing unreacted monomers and small molecule impurities, avoiding side reactions in the electrolyte caused by impurities, SEI film damage, and ensuring the ultra-high purity and electrochemical inertness of the negative electrode binder.

[0063] In practice, the preparation method includes the following steps:

[0064] In a nitrogen atmosphere and a sealed reactor, the stirring is turned on and operated at a constant speed of 200 r / min to 300 r / min. The organic crosslinking agent, the interface activating monomer, and the hydroxyl-containing acrylate monomer are mixed to obtain the first mixture. The mixture is stirred for 20 min to 30 min until it is completely dissolved and dispersed to form a uniform and transparent bottom liquid. High-purity nitrogen is continuously introduced for 15 min to 30 min to remove oxygen, and the first reaction liquid is obtained. The addition ratio of the organic crosslinking agent, the interface activating monomer, and the hydroxyl-containing acrylate monomer is (0.5 to 4): (3 to 8): (2 to 5).

[0065] The first reaction solution is heated to 65℃~80℃, and the first initiator aqueous solution is added. The mixture is stirred at 200r / min~300r / min for 15min~30min to carry out the prepolymerization reaction and obtain the second reaction solution (polymer seed solution).

[0066] Under conditions of 180 r / min to 300 r / min, a second mixture containing aliphatic acrylate monomers, alicyclic acrylate monomers, and olefinic acid monomers, and an aqueous solution of a second initiator were simultaneously added dropwise to the second reaction solution using dual constant flow pumps. The dropwise addition time was controlled to be 3 h to 4 h. After the dropwise addition was completed, the reaction system was heated to 65 °C to 80 °C for polymerization reaction and kept at this temperature for 2 h to 3 h to obtain the third reaction solution. The mass ratio of the second mixture to the first mixture was (0.5 to 2): (0.5 to 2), and the addition ratio of aliphatic acrylate monomers, alicyclic acrylate monomers, and olefinic acid monomers was (10 to 20): (5 to 12): (55 to 75).

[0067] Optionally, after the polymerization reaction is completely finished and the third reaction liquid system is cooled to 40℃~50℃, an inorganic crosslinking agent is slowly added (the mass ratio of organic crosslinking agent to inorganic crosslinking agent is (1~5):1) to obtain a reaction liquid containing polymer;

[0068] The reaction solution containing the polymer was cooled at a rate of 3℃ / h to 5℃ / h, the solid content of the reaction solution was adjusted with deionized water, the pH of the reaction solution was adjusted with a pH adjuster, and after filtration, the above-mentioned negative electrode binder was obtained.

[0069] The aforementioned pH adjuster includes ammonia water, which has the advantages of being volatile, leaving no residue, and providing gentle pH adjustment.

[0070] Specifically, the reaction solution is filtered through a filter screen with a filtration precision of 400-600 mesh, such as 400 mesh, 450 mesh, 500 mesh, 550 mesh, 600 mesh, or any combination thereof.

[0071] Specifically, the pH of the aforementioned negative electrode binder is 7.0 to 8.5, for example, a range consisting of 7.0, 7.4, 7.8, 8, 8.2, 8.5, or any two of these.

[0072] Specifically, the polymerization reaction temperature can be 65℃~80℃, for example, 65℃, 69℃, 70℃, 73℃, 77℃, 80℃, or any combination thereof. When the initiator used in the preparation process is a thermally decomposable initiator system, the polymerization reaction temperature can be 75℃~80℃. In the temperature range of 75~80℃, the thermally decomposable initiator system has high activity, fast reaction rate, and the overall polymerization cycle (dropping + heat preservation) can be shortened, resulting in higher yield per unit time and reducing the cost of industrial mass production. When the initiator used in the preparation process is a redox initiator system, the polymerization reaction temperature can be 65℃~70℃. The low temperature range is suitable for redox initiation systems, protecting the structure of alicyclic acrylate monomers and hydroxyl-containing acrylate monomers.

[0073] In addition, the total time for the dripping and polymerization reaction is controlled to be 5 to 7 hours to avoid problems such as localized rapid polymerization, excessively wide molecular weight distribution, and uneven cross-linking, thus ensuring the consistency of product performance across batches.

[0074] Specifically, the mass of the first initiator mentioned above accounts for 10% to 20% of the total mass of the initiator, for example, 10%, 12%, 14%, 16%, 18%, 20%, or any combination thereof. If the mass percentage is less than 10%, the initial free radical concentration is too low, resulting in fewer polymerization seeds and uneven particle size. This makes it easy for new nuclei to continuously form during subsequent addition of the main monomer, leading to an excessively wide molecular weight distribution and large fluctuations in product performance. If the mass percentage is greater than 20%, the initial free radical concentration is too high, resulting in too many seeds. This leads to a lower final polymer molecular weight, decreased cohesive strength and resistance to electrolyte swelling, and concentrated exothermic activity during the prepolymerization stage, posing a risk of localized explosive polymerization.

[0075] Specifically, the mass of the second initiator accounts for 80% to 90% of the total mass of the initiator, for example, a range consisting of 80%, 82%, 84%, 86%, 88%, 90%, or any two of these.

[0076] This invention also provides a negative electrode sheet, including a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, wherein the negative electrode active material layer includes the aforementioned negative electrode binder.

[0077] According to the inventors' research, the negative electrode sheet provided in this embodiment of the invention uses the above-mentioned organic-inorganic dual crosslinked negative electrode binder to prepare the negative electrode active material layer. The negative electrode binder is uniformly dispersed in the aqueous slurry, and the interface activation structural unit can form preliminary hydrogen bond interaction with the surface of silicon carbon active particles. The slurry has excellent stability and is not prone to component stratification and particle sedimentation. During the coating and drying process, organic permanent covalent crosslinking and inorganic dynamic borate ester crosslinking are formed simultaneously and uniformly, and the negative electrode binder is not prone to directional migration to the electrode surface. After drying, a uniform and continuous dual crosslinked bonding network can be constructed in the thickness direction of the electrode sheet, which can adapt to the charge and discharge volume deformation of silicon carbon materials, while strengthening the interfacial bonding strength and anti-electrolyte swelling performance, and maintaining the structural integrity and electrochemical stability of the electrode sheet for a long time.

[0078] Specifically, the aforementioned negative electrode active material layer includes a negative electrode active material; the aforementioned negative electrode active material can be selected from conventional materials in the art, such as silicon-based materials. Silicon-based materials have high theoretical specific capacity and are the core negative electrode material for high-energy-density lithium-ion batteries. While achieving high specific capacity of the negative electrode, the adaptability of the negative electrode binder effectively alleviates the problems of electrode structure pulverization and active material shedding caused by the volume expansion of silicon-based materials. Specifically, the aforementioned silicon-based material includes silicon and / or silicon composite materials, and the aforementioned silicon composite materials include one or more of silicon oxides and silicon-carbon composites.

[0079] The aforementioned negative electrode active material layer also includes conductive agents and / or thickeners.

[0080] Specifically, the conductive agent in the negative electrode sheet of the present invention can be selected from conventional materials in the art. For example, the conductive agent includes one or more of conductive carbon black, acetylene black, conductive graphite, carbon nanotubes, graphene, Ketjen black, and carbon fiber, and there are no particular limitations on this.

[0081] The thickener used in this embodiment of the invention may be selected from conventional materials in the art, such as sodium carboxymethyl cellulose (CMC).

[0082] The embodiments of the present invention may be selected from conventional negative electrode current collectors in the art, for example, negative electrode current collectors include copper foil.

[0083] In this embodiment of the invention, the negative electrode sheet can be prepared by conventional methods in the art, such as by coating. Specifically, the negative electrode active material, negative electrode binder, conductive agent and other components used to form the negative electrode active material layer can be dispersed in a solvent. The amount of each raw material added is conventional in the art. The negative electrode slurry is prepared and then coated on the surface of the negative electrode current collector. After drying, rolling and other processes, the negative electrode sheet is obtained.

[0084] In the negative electrode slurry, the mass fraction of the negative electrode binder is 1.5% to 5%, for example, 1.5%, 2%, 2.5%, 3%, 4%, 5% or any combination thereof.

[0085] This invention also provides a battery comprising the aforementioned negative electrode sheet.

[0086] According to the inventors' research, assembling batteries using the above-mentioned negative electrode sheets can significantly suppress interfacial failure behaviors such as electrode sheet cracking and active material shedding caused by the expansion and contraction of silicon-carbon negative electrodes during charging and discharging, reduce interfacial charge transfer impedance, reduce electrolyte side reactions and irreversible lithium loss, and have the overall advantages of higher first-cycle coulombic efficiency, stable ion transport capability and excellent long-cycle capacity retention, significantly improving the defects of silicon-carbon system batteries such as rapid cycle decay and insufficient electrochemical stability.

[0087] Specifically, the battery can be a single cell or a battery pack. The battery pack includes at least two interconnected single cells. These single cells can be electrically connected by conventional methods in the art, such as series connection, parallel connection, or a hybrid connection that includes both of these connection methods. No particular limitation is made in this regard.

[0088] Specifically, a battery includes a cell and a casing that encapsulates the cell. The cell includes a positive electrode, a separator, and a negative electrode.

[0089] In this embodiment of the invention, the battery cell can be packaged using conventional housing materials in the art, such as flexible packaging materials like aluminum-plastic film, but is not limited thereto.

[0090] Generally, a positive electrode sheet includes a positive current collector and a positive electrode coating located on at least one side surface of the positive current collector. Specifically, the positive electrode coating can be provided on one side surface of the positive current collector, or the positive electrode coating can be provided on opposite sides of the positive current collector in the thickness direction (i.e., the positive and negative surfaces of the positive current collector).

[0091] Specifically, the positive electrode coating includes materials such as positive electrode active material, positive electrode binder, and conductive agent, all of which can be conventional materials in the art. For example, the battery described above is a lithium-ion battery, and the positive electrode active material may include lithium-containing positive electrode active material, specifically including one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, and ternary positive electrode materials. The ternary positive electrode material may include nickel-cobalt-manganese ternary materials and / or nickel-cobalt-aluminum ternary materials.

[0092] In addition, the conductive agent in the positive electrode coating may include one or more of the following: conductive carbon black, conductive graphite, carbon nanotubes, acetylene black, graphene, Ketjen black, and carbon fiber.

[0093] In addition, the positive electrode binder in the positive electrode coating may be one or more of the following: polyvinylidene fluoride, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, etc.

[0094] In this embodiment of the invention, conventional positive current collectors in the art can be used, for example, the positive current collector includes aluminum foil.

[0095] In this embodiment of the invention, the positive electrode sheet can be prepared by conventional methods in the art, such as by coating. Specifically, the positive electrode active material, conductive agent, positive electrode binder, and other components used to form the positive electrode active material layer can be dispersed in a positive electrode solvent, such as N-methylpyrrolidone. The amount of each raw material added is conventional in the art, and a positive electrode slurry is prepared. This slurry is then coated onto the surface of the positive electrode current collector, and after drying, rolling, and other processes, the positive electrode sheet is obtained. The coating, drying, and rolling processes involved are conventional operations for preparing positive electrode sheets using the coating method, and are not particularly limited thereto.

[0096] In this embodiment of the invention, the battery can be prepared by conventional methods in the art. The preparation process may include: assembling the positive electrode, separator, and negative electrode layers into a cell, and then encapsulating the electrolyte in a casing, etc., to obtain the battery. All the processes involved are conventional battery preparation processes and are not particularly limited.

[0097] In this invention, the electrolyte comprises lithium salt, organic solvent and additives, wherein the lithium salt is lithium hexafluorophosphate (LIPF6) and its concentration in the electrolyte is 1 mol / L; the organic solvent is composed of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:4:3.

[0098] This invention also provides an electrical device, including the battery described above.

[0099] According to the inventor's research, using the aforementioned stable battery as the power supply unit ensures a long-term stable power supply for electrical equipment due to the battery's long cycle life and high capacity, reducing the frequency of battery replacement and improving the user experience.

[0100] The electrical equipment used in the embodiments of the present invention can be conventional electrical equipment in the art, such as power equipment (e.g., electric vehicles, electric cars), electronic equipment (e.g., mobile phones, tablets, laptops, digital cameras, etc.), wearable devices (e.g., watches, bracelets, VR glasses, etc.), energy storage power stations, etc., and there are no particular limitations on this.

[0101] The present invention will be further described below through specific embodiments. The isosorbide monoacrylate and glycerol monoacrylate used in the embodiments and comparative examples were prepared by the following method:

[0102] Preparation of isosorbide monoester acrylate:

[0103] Ingredient mixing: Isosorbide and acrylic acid are used as reactants and added in a molar ratio of 1:0.8 to 1:1 (isosorbide is added in excess to inhibit the formation of diester byproducts); toluene is added as a dehydrating agent, p-toluenesulfonic acid as an acidic catalyst, and hydroquinone as a free radical polymerization inhibitor.

[0104] Segmented esterification: First, heat to 110~120℃ and reflux under normal pressure to remove water for 1~2 hours; then adjust the vacuum of the system to 0.05~0.06MPa and react under reduced pressure for 2~3 hours, continuously removing the generated water to promote complete esterification.

[0105] Post-treatment purification: The reaction solution is neutralized with dilute alkali and washed with water to remove the catalyst and residual acid. Then, it is removed by vacuum distillation to remove the water-carrying agent and light components, yielding isosorbide monoester of acrylate. The selectivity of the monoester can reach more than 90%.

[0106] Preparation of glycerol monoacrylate:

[0107] Using glycerol and acrylic acid as raw materials, with glycerol in a large excess (molar ratio of about 3:1), p-toluenesulfonic acid / concentrated sulfuric acid as catalyst, hydroquinone as polymerization inhibitor, and cyclohexane as dehydrating agent, the reaction is carried out under reflux at 80~110℃ to remove water. After the reaction is completed, the excess glycerol and solvent are removed by neutralization to obtain industrial grade glycerol monoacrylate with a monoacrylate content of ≥85%.

[0108] Example 1

[0109] The monomer raw materials used in the preparation of the negative electrode binder, by mass, include: 69 parts acrylic acid (acrylic acid monomer), 15 parts butyl acrylate (aliphatic acrylate monomer), 8 parts modified adamantane acrylate (alicyclic acrylate monomer), 5 parts maleic anhydride (interface activating monomer), and 3 parts isosorbide monoacrylate (hydroxyl-containing acrylate monomer).

[0110] The total amount of crosslinking agent added accounts for 2.5% of the total mass of monomer raw materials. Only 2.5 parts of trimethylolpropane triacrylate (TMPTA, organic crosslinking agent) are used, and no boric acid inorganic crosslinking agent is added. The total amount of ammonium persulfate initiator accounts for 0.8% of the total mass of monomer raw materials. The mass ratio of the first initiator to the second initiator is 15:85, that is, 0.12 parts of the first ammonium persulfate and 0.68 parts of the second ammonium persulfate.

[0111] S1, Preparation of negative electrode binder

[0112] In a nitrogen atmosphere and a sealed reactor, the stirring is turned on and the stirring speed is 220 r / min. The above trimethylolpropane triacrylate, maleic anhydride and isosorbide monoacrylate are mixed and stirred for 25 min until completely dissolved and dispersed to form a uniform and transparent bottom liquid. High-purity nitrogen is continuously introduced for 30 min to remove oxygen and obtain the first reaction liquid.

[0113] The first reaction solution was heated to 75°C, and the first ammonium persulfate was added. The mixture was stirred at 280 r / min for 20 min to carry out the prepolymerization reaction and obtain the second reaction solution (polymer seed solution).

[0114] At 220 r / min, a mixture containing butyl acrylate, acrylate-modified adamantane ester, acrylic acid, and a second ammonium persulfate aqueous solution was simultaneously added dropwise to the second reaction solution using a dual constant flow pump. The dropwise addition time was controlled to be 3.5 h. After the dropwise addition was completed, the reaction system was heated to 75 °C to carry out the polymerization reaction and kept at the temperature for 2.5 h to obtain a reaction solution containing polymer.

[0115] The polymer-containing reaction solution was cooled at a rate of 4℃ / h. The solid content and pH of the reaction solution were adjusted using deionized water and ammonia. After filtration through a 500-mesh filter, the negative electrode binder was obtained. The negative electrode binder had a solid content of 20% and a viscosity of 4600 mPa at 25℃. The pH is 7.5; the glass transition temperature of the polymer is 1℃.

[0116] S2, Battery Preparation

[0117] S2-1, Preparation of negative electrode sheet:

[0118] By weight, 92 parts of silicon-carbon composite material with 10% silicon content, 3 parts of conductive carbon black, and 5 parts of the negative electrode binder prepared in step S1 were mixed and stirred at 15 rpm for 20 min. Deionized water was added simultaneously to adjust the solid content of the mixture (the percentage of the total mass of the components other than the solvent in the mixed solution) to 48 wt%. The mixture was then pre-stirred at 40 rpm for 60 min, followed by kneading. Finally, after vacuum defoaming for 30 min, the mixture was discharged to obtain the negative electrode slurry. The obtained negative electrode slurry was coated on both sides of the copper foil of the negative electrode current collector, with a single-sided coating surface density of 110 g / m². 2 After processes such as drying, cold pressing, slitting, and welding of electrode tabs, a compacted density of 1.6 g / cm³ is obtained. 3 The negative electrode.

[0119] S2-2, Lithium-ion battery preparation:

[0120] The above-mentioned negative electrode, separator (PE film), ternary positive electrode (NCM811) and electrolyte are assembled to obtain a coin cell. The electrolyte includes lithium salt, organic solvent and additives, wherein the lithium salt is lithium hexafluorophosphate (LIPF6) and its concentration in the electrolyte is 1 mol / L; the organic solvent is a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:4:3.

[0121] Example 2

[0122] The monomer raw materials used in the preparation of the negative electrode binder, by mass, include: 69 parts of acrylic acid (acrylic monomer), 15 parts of butyl acrylate (aliphatic acrylate monomer), 8 parts of modified adamantane acrylate (alicyclic acrylate monomer), 5 parts of maleic anhydride (interface activating monomer), and 3 parts of isosorbide monoacrylate (hydroxyl-containing acrylate monomer).

[0123] The crosslinking agent accounts for 2.5% of the total mass of the monomer raw materials. The mass ratio of trimethylolpropane triacrylate (organic crosslinking agent) to boric acid (inorganic crosslinking agent) is 3:1, that is, 1.875 parts of trimethylolpropane triacrylate and 0.625 parts of boric acid. The sum of the masses of ammonium persulfate (first initiator) and ammonium persulfate (second initiator) accounts for 0.8% of the total mass of the monomer raw materials. The mass ratio of the first initiator to the second initiator is 15:85, that is, 0.12 parts of ammonium persulfate and 0.68 parts of ammonium persulfate.

[0124] S1, Preparation of negative electrode binder

[0125] In a nitrogen atmosphere and a sealed reactor, the stirring is turned on and the stirring speed is 220 r / min. The above trimethylolpropane triacrylate, maleic anhydride and isosorbide monoacrylate are mixed and stirred for 25 min until completely dissolved and dispersed to form a uniform and transparent bottom liquid. High-purity nitrogen is continuously introduced for 30 min to remove oxygen and obtain the first reaction liquid.

[0126] The first reaction solution was heated to 75°C, and the first ammonium persulfate was added. The mixture was stirred at 280 r / min for 20 min to carry out the prepolymerization reaction and obtain the second reaction solution (polymer seed solution).

[0127] Under conditions of 220 r / min, a mixture containing butyl acrylate, acrylate-modified adamantane ester, and acrylic acid, and an aqueous solution of ammonium persulfate were simultaneously added dropwise to the second reaction solution using dual constant flow pumps. The dropwise addition time was controlled to be 3.5 h. After the dropwise addition was completed, the reaction system was heated to 75 °C to carry out the polymerization reaction and kept at the temperature for 2.5 h to obtain the third reaction solution.

[0128] After the polymerization reaction is completely completed and the third reaction solution system is cooled to 45°C, boric acid aqueous solution is slowly added to obtain a reaction solution containing polymer.

[0129] The polymer-containing reaction solution was cooled at a rate of 4℃ / h, and the reaction solution was adjusted with deionized water. After filtration through a 500-mesh filter, the negative electrode binder was obtained. The negative electrode binder had a solid content of 20% and a viscosity of 5000 mPa at 25℃. The pH value is 7.5; the glass transition temperature of the polymer is 2℃.

[0130] S2, Battery Preparation

[0131] S2-1, Preparation of negative electrode sheet:

[0132] By weight, 92 parts of silicon-carbon composite material with 10% silicon content, 3 parts of conductive carbon black, and 5 parts of the negative electrode binder prepared in step S1 were mixed and stirred at 15 rpm for 20 min. Deionized water was added simultaneously to adjust the solid content of the mixture (the percentage of the total mass of the components other than the solvent in the mixed solution) to 48 wt%. The mixture was then pre-stirred at 40 rpm for 60 min, followed by kneading. Finally, after vacuum defoaming for 30 min, the mixture was discharged to obtain the negative electrode slurry. The obtained negative electrode slurry was coated on both sides of the copper foil of the negative electrode current collector, with a single-sided coating surface density of 110 g / m². 2 After processes such as drying, cold pressing, slitting, and welding of electrode tabs, a compacted density of 1.6 g / cm³ is obtained. 3 The negative electrode.

[0133] S2-2, Lithium-ion battery preparation:

[0134] The above-mentioned negative electrode, separator (PE film), ternary positive electrode (NCM811) and electrolyte are assembled to obtain a coin cell. The electrolyte includes lithium salt, organic solvent and additives, wherein the lithium salt is lithium hexafluorophosphate (LIPF6) and its concentration in the electrolyte is 1 mol / L; the organic solvent is a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:4:3.

[0135] The differences between Examples 3 to 21, Comparative Examples 1 to 6 and Example 1 are detailed in Tables 1 and 2. The remaining preparation conditions are the same as those in Example 1.

[0136] Table 1

[0137]

[0138]

[0139] Table 2

[0140]

[0141]

[0142] The performance of the negative electrode binder, negative electrode sheet, and battery in each embodiment and comparative example was tested through the following process.

[0143] (1) Glass transition temperature (Tg) test: The glass transition temperature (Tg) of the polymer was detected using a differential scanning calorimeter (DSC214Polyma). Before the test, the negative electrode binder sample was pretreated: the negative electrode binder was placed in a vacuum drying oven and dried at 60℃ for 12h to completely remove deionized water, and then pulverized and ground into a powder solid; high-purity nitrogen was turned on and its flow rate was controlled at 0.6L / min, and then the DSC instrument and control system were started. The temperature program was set as follows: initial temperature -60℃, constant temperature for 10min to eliminate thermal history; then scanning was performed in the temperature range of -60℃ to 80℃ at a heating rate of 10K / min; after the program was set, the sample was placed in the heating furnace, the furnace lid was sealed, and an appropriate amount of liquid nitrogen was added to the constant temperature tank to ensure the low temperature environment was started. When the sample chamber temperature stabilized at -60℃, i.e. the second heating curve, the test program could be run and data acquisition could begin. The glass transition temperature (Tg) of the polymer was read from the position of the abrupt change of the curve step.

[0144] (2) Viscosity test: The apparent viscosity of the negative electrode binder at 25°C was determined using a Brookfield rotational viscometer. The binder sample was kept at 25°C and rotated at 20 r / min. The sample was poured into the measuring container, with the liquid level above the rotor scale. The container was kept at a constant temperature for 15 min to eliminate air bubbles. The instrument was started, and the viscosity value was recorded after the reading stabilized for 30 s. The same sample was tested in parallel 3 times, and the average value was taken as the final viscosity result.

[0145] (3) Swelling test: The negative electrode binder was poured into a 15cm×18cm fixed mold, air-dried for 12 hours, and then vacuum-dried at 60℃ for 12 hours to remove residual moisture, resulting in a polymer film. The film was cut into 10mm×20mm samples, and the initial mass m0 of the film was weighed. The film was completely immersed in lithium-ion battery electrolyte (EC:DMC:EMC=3:4:3, 1mol / L LiPF6), sealed, and placed in a 60℃ constant temperature oven for 72 hours. After immersion, the film was removed, and the free electrolyte on the surface was quickly wiped away with a dust-free filter paper. The mass m after swelling was weighed. t The formula for calculating the swelling ratio is: Swelling ratio (%) = (m t -m0) / m0×100%, three samples were tested in parallel for each group, and the average value was taken.

[0146] (4) Peel strength test of negative electrode sheet: The peel strength of negative electrode sheet at 180° was tested in accordance with GB / T2792-2014 standard. The prepared negative electrode sheet was cut into standard test strips with a width of 25mm and a length of 150mm. The test was carried out using an electronic universal testing machine (WDW-50E). The peel rate was set to 100mm / min to ensure that the effective peel length was not less than 100mm. Five samples were prepared in parallel for each group to complete the repeated test. Finally, the average value of the five test data was taken as the peel strength result of the sample. The unit of measurement is N / m.

[0147] (5) Flexibility test of negative electrode sheet: The electrode bending test device (PR-BDM-100P) and optical microscope (ZEISS) were used to complete the electrode sheet flexibility test. The negative electrode sheet to be tested was cut into strips with a width of 20mm and a length of 100mm. A stainless steel cylindrical rod with a diameter of 5mm was selected as the bending base. The electrode sheet was bent back and forth along the cylindrical rod for 180°. After 20 consecutive bending cycles, the surface condition of the electrode sheet was checked by combining visual observation with microscopic observation under an optical microscope. The flexibility evaluation level was divided into three grades: excellent, good, and average, based on the occurrence of surface cracks.

[0148] (6) Battery capacity retention rate test after 200 cycles: The constant current charge and discharge cycle performance of the battery was tested in accordance with the two national standards GB / T30038-2013 and GB / T36276-2018. The assembled button battery was tested using the Blue Electric high-precision battery testing system. The battery charge and discharge voltage range was set to 2.75V~4.25V and the charge and discharge rate was 1C. The test procedure was to first charge to 4.25V with 1C constant current, let it stand for 5 minutes, and then discharge to 2.75V with 1C constant current. Each charge and discharge process was recorded as one complete cycle. 200 cycles were continuously completed. The capacity retention rate after 200 cycles was calculated according to the formula: capacity retention rate = (capacity of discharge after 200 cycles ÷ capacity of discharge after first cycles) × 100%.

[0149] (7) Electrode Interfacial Impedance (EIS) Test: Electrochemical impedance spectroscopy (EIS) test of electrode interfacial impedance was performed using an electrochemical workstation. Coin cells that had undergone activation treatment and been allowed to stand until their performance was stable were selected as test samples. The AC perturbation voltage amplitude was set to 5 mV, and the test scan frequency range was 10 mV. -2 Hz~10 5 The high-frequency region values ​​in the impedance spectrum curve were collected as the electrode interface impedance results. Each group of samples was tested in parallel for 3 times. The average value of the 3 sets of test data was taken as the electrode interface impedance of the system, and the unit of measurement was Ω.

[0150] (8) Rate performance test: The same CR2032 coin cell as the electrochemical cycle performance test was used and placed in a constant temperature environment of 25℃ for 24h. The battery test system was used to perform charge and discharge rate tests in the order of 0.1C, 0.5C, 1C, 2C, 3C, 4C and 0.5C. Each rate was cycled 3 times and the discharge capacity at different rates was recorded. Three parallel batteries were set up for each test group and the average value was taken as the final test result.

[0151] Table 3

[0152]

[0153]

[0154] As can be seen from Table 3, Examples 1 to 21, which contain acrylate structural units, aliphatic acrylate structural units, alicyclic acrylate structural units, hydroxyl-containing acrylate structural units, interface-activated structural units, and organic crosslinking structural units, have significantly better overall performance than the comparative examples.

[0155] Comparative Example 1, a pure linear polyacrylic acid system, lacks all functional structural units and cross-linking design. Its electrode's 180° peel strength is only 5.7 N / m, its capacity retention after 200 cycles is only 65.20%, and its electrolyte swelling rate is as high as 135%, resulting in significantly inferior performance across the board. This verifies the necessity of a synergistic design of multiple structural units. Comparative Example 2, lacking organic cross-linking structural units, can only form a linear polymer. Its electrode peel strength drops to 9.7 N / m, its cycle capacity retention is only 81.50%, and its interfacial impedance rises to 45.8 Ω, indicating that organic cross-linking structural units are the core components for constructing a stable three-dimensional network and ensuring structural strength and long-term interfacial stability. Comparative Example 3, lacking aliphatic acrylate structural units, shows a significant decrease in electrode flexibility, with microcracks appearing after repeated bending, making it difficult to adapt to the repeated volume deformation of silicon-carbon materials. Comparative Example 4, lacking alicyclic acrylate structural units, shows an electrolyte swelling rate of 90%, significantly weakening its resistance to electrolyte erosion. Comparative Example 5, lacking the interface activation structural unit, saw its electrolyte swelling rate further increase to 94%, indicating insufficient long-term stability of the solid-solid interface bonding. Comparative Example 6, lacking the hydroxyl-containing acrylate structural unit, had an electrolyte swelling rate of 84%, failing to leverage the synergistic effect of enhanced interface adhesion and assisted cross-linking. Therefore, it is evident that the synergistic effect and mutual support of the structural units in this invention, combined with proper formulation, are essential to simultaneously achieve high bonding strength, excellent deformation adaptability, strong anti-swelling ability, and long-term cycling stability.

[0156] Further analysis of the example data shows that, within the range of mass ratios of structural units, glass transition temperatures of polymers, polymer viscosity and solid content, and crosslinking ratios defined by this invention, each group of examples maintains balanced and excellent overall performance. Comparing Example 1 and Example 2, it is evident that after introducing inorganic crosslinking groups to form a double-crosslinked system based on organic covalent crosslinking, the capacity retention rate after 200 cycles in Example 2 increased from 90.10% to 92.30%, the electrolyte swelling rate decreased from 78% to 56%, and the interfacial impedance further decreased, verifying the role of the double-crosslinked network in improving structural stability and interfacial performance. Examples 3 to 9 cover different monomer types and ratio gradients, and each group achieves stable performance. Groups with ratios closer to the middle value exhibit better overall performance; groups with ratios closer to the boundary of the range show a corresponding decrease in flexibility or slight fluctuations in bonding strength. Examples 10-13 represent a solid content gradient group. Examples 10 and 11, with solid content ranging from 15% to 25%, exhibit moderate system viscosity and balanced slurry suspension stability and coating compatibility. Examples 12 (27%) and 13 (13%), with solid content exceeding this range, show viscosity deviations from the suitable processing range, resulting in a significantly narrowed process window. Examples 14-17 represent a glass transition temperature gradient group. Examples 14 and 15, with Tg ranging from -5℃ to 15℃, simultaneously provide rigid support and deformation buffering capacity. Examples 16 (below -5℃) and 17 (above 15℃) exhibit decreased anti-swelling performance or reduced electrode flexibility, respectively. Examples 18-21 represent a viscosity gradient group, with viscosity ranging from 2000 to 20000 mPa at 25℃. Examples 18 and 19, within the s range, show a good match between slurry flow properties and suspension capacity; Examples 20 and 21, with viscosity exceeding this range, show an increased risk of slurry sedimentation or difficulty in coating processing.

[0157] In summary, this invention, through the precise matching of multiple functional structural units and the basic support of an organic cross-linked network, enables the binder to simultaneously possess excellent interfacial bonding strength, deformation buffering capacity, anti-electrolyte swelling performance, and structural stability. This effectively alleviates the problems of large volume deformation and interfacial failure during the charging and discharging process of silicon-carbon anodes, significantly improves the long cycle life and rate performance of the electrodes, and meets the industrial application requirements of high-energy-density silicon-carbon anodes.

[0158] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A negative electrode binder, characterized in that, The polymers include acrylic acid structural units, aliphatic acrylate structural units, alicyclic acrylate structural units, hydroxyl-containing acrylate structural units, interface-activated structural units, and organic crosslinking structural units. The interface activation structural unit includes anhydride structural units.

2. The negative electrode binder according to claim 1, characterized in that, In the polymer, the mass ratio of the olefinic structural unit, the aliphatic acrylate structural unit, the alicyclic acrylate structural unit, the hydroxyl-containing acrylate structural unit, the interface-activated structural unit, and the organic crosslinking structural unit is (55~75):(10~20):(5~12):(2~5):(3~8):(0.5~4).

3. The negative electrode binder according to claim 1 or 2, characterized in that, The olefinic structural units include one or more of the following: itaconic acid structural units, fumaric acid structural units, citraconic acid structural units, acrylic acid structural units, and methacrylic acid structural units. And / or, the aliphatic acrylate structural unit includes one or more of butyl acrylate structural units, ethyl acrylate structural units, and isooctyl acrylate structural units; And / or, the alicyclic acrylate structural unit includes one or more of the following: acrylic acid-modified adamantane ester structural unit, isobornyl acrylate structural unit, and tricyclodecanediethanol diacrylate structural unit; And / or, the hydroxyl-containing acrylate structural unit includes one or more of isosorbide acrylate structural units and glyceryl acrylate structural units.

4. The negative electrode binder according to claim 1 or 2, characterized in that, The anhydride structural units in the interface activation structural unit include one or more of maleic anhydride structural units, succinic anhydride structural units, itaconic anhydride structural units, and methacrylic anhydride structural units.

5. The negative electrode binder according to claim 1 or 2, characterized in that, The polymer also includes inorganic crosslinking groups attached to the polymer molecular chain.

6. The negative electrode binder according to claim 5, characterized in that, In the polymer, the mass ratio of the organic crosslinking structural unit to the inorganic crosslinking group is (1~5):1; And / or, the organic crosslinking structural unit includes one or more of the following: trimethylolpropane triacrylate structural unit, pentaerythritol triacrylate structural unit, dipropylene glycol diacrylate structural unit, and itaconic acid diacrylate structural unit; And / or, the inorganic crosslinking groups include borate ester groups.

7. The negative electrode binder according to claim 1 or 2, characterized in that, The glass transition temperature of the polymer is -5℃ to 15℃.

8. The negative electrode binder according to claim 1 or 2, characterized in that, The viscosity of the negative electrode binder is 2000 mPa. s~20000mPa s; And / or, the solid content of the negative electrode binder is 15%~25%.

9. A negative electrode sheet, characterized in that, It includes a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, the negative electrode active material layer including the negative electrode binder according to any one of claims 1 to 8.

10. A battery, characterized in that, Includes the negative electrode sheet as described in claim 9.